Effect of Music Oxygen Bar on the Rehabilitation of Traumatic Pelvic Fracture Patients - Lan LI; Wei YANG (康复学报)
Objective:To investigate rehabilitation effect of music oxygen bar on traumatic pelvic fracture patients.Methods:A total of 113 patients who underwent therapy for traumatic pelvic fracture in our hospital were selected as study subjects and divided into observation group and control group according to random number table with 57 cases and 56 cases respectively. The control group was treated by traditional protocol of rehabilitation nursing, while the observation group received"music oxygen bar"nursing on the basis of the control group. The self-made scale was applied to evaluate the enthusiasm of rehabilitation training, VAS standard pain score and SDS/SAS negative emotion status (including depression, anxiety) and Matta score was used.Results:VAS pain score of the observation group patients was significantly lower than that of the control group patients after two weeks'treatment, with statistically significant (P<0.05). SDS depression score and SAS anxiety score of the observation group were significantly lower than those of the control group (all P<0.05). The enthusiasm of rehabilitation training in the observation group was significantly higher than that of the control group (P<0.05). The excellent rate of rehabilitation in the observation group was significantly better than in the control group (P<0.05).Conclusion:Music oxygen bar care can improve patients'enthusiasm and effect of rehabilitation training on traumatic pelvic fracture, reduce their pain and incidence of negative emotion.